MISKONSEPSI MAHASISWA PENDIDIKAN FISIKA PADA MATERI EFEK FOTOLISTRIK - Restina Muji Mulyanti; Agus Yulianto; Budi Astuti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
An understanding of the photoelectric effect is the key to understanding the basics of quantum physics. The photoelectric effect can explain the quantization of energy that cannot be explained using classical physics theory. This study aims to determine the level of understanding of the concept of sixth semester physics education students of Semarang State University about the photoelectric effect. The data collection method used is a test method that contains a number of questions to reveal the students' conception of the photoelectric effect. Data analysis techniques in this study are quantitative and qualitative analysis. The results showed that as many as 61% -64% of students still had difficulty in distinguishing the effect of the frequency and intensity of light on the photoelectric effect. In addition, more than 83% of students have not been able to understand the function of the potential difference given between the cathode and anode plate in the photoelectric effect experiment. Based on the results of this study, it can be concluded that the level of understanding of the concept of students is still low, which is characterized by the existence of several types of misconceptions about the photoelectric effect.